IDENTIFIKASI KANDUNGAN KIMIA EKSTRAK ETANOL LIMBAH DAUN KUBIS (Brassica oleracea L.) - Andi Wijaya; Fitria Anggraini (Jurnal Komunitas Farmasi Nasional, 2023)
Cabbage (Brassica oleracea L.) is one of the most common vegetable commodities in Indonesia so cabbage dominates vegetable waste in traditional markets which is used as animal feed. To be developed as a traditional medicinal material, it is necessary to know the content of secondary metabolite compounds qualitatively. This study aims to determine the secondary metabolite compounds from cabbage leaf waste qualitatively through phytochemical screening and Thin Layer Chromatography (KLT) analysis. Extraction was carried out using 95% ethanol solvent by remaseration. Testing the content of secondary metabolites in ethanol extracts of cabbage leaf waste was carried out by phytochemical screening. Furthermore, the KLT test with stationary phase silica GF 254 and mobile phase chloroform: methanol: water with a ratio of 64:50:10. The results of the study were analyzed descriptively. The results obtained extract yield of 3.03%. The ethanol extract of cabbage waste contains saponin and steroid compounds. In the results of KLT analysis, there are 2 spots with Rf 0.75 and 0.875 which are green when observed visually and blue with UV light observation 366 nm which indicates the presence of saponin and steroid compounds. This study shows that the ethanol extract of cabbage leaf waste contains secondary metabolite compounds, namely saponins and steroids.. Keywords : phytochemical, screening, Brassica oleracea L.